Effects of respiratory muscle work on blood flow distribution during exercise in heart failure - Olson, Thomas P (Blackwell Science Inc, 2010)
Heart failure (HF) patients have a reduced cardiac reserve and increased work of breathing. Increased locomotor muscle blood flow demand may result in competition between respiratory and locomotor vascular beds. We hypothesized that HF patients would demonstrate improved locomotor blood flow with respiratory muscle unloading during activity. Ten patients (ejection fraction = 31 ± 3%) and 10 controls (CTL) underwent two cycling sessions (60% peak work). Session 1 (S1): 5 min of normal breathing (NB), 5 min respiratory muscle unloading with a ventilator, and 5 min of NB. Session 2 (S2): 5 min NB, 5 min of respiratory muscle loading with inspiratory resistance, and 5 min of NB. Measurements included: leg blood flow (LBF, thermodilution), cardiac output [Image: see text], and oesophageal pressure (P(pl), index of pleural pressure). S1: P(pl) was reduced in both groups (HF: 73 ± 8%; CTL: 60 ± 13%, P < 0.01). HF: [Image: see text] increased (9.6 ± 0.4 vs. 11.3 ± 0.8 l min(−1), P < 0.05) and LBF increased (4.8 ± 0.8 vs. 7.3 ± 1.1 l min(−1), P < 0.01); CTL: no changes in [Image: see text] (14.7 ± 1.0 vs. 14.8 ± 1.6 l min(−1)) or LBF (10.9 ± 1.8 vs. 10.3 ± 1.7 l min(−1)). S2: P(pl) increased in both groups (HF: 172 ± 16%, CTL: 220 ± 40%, P < 0.01). HF: no change was observed in [Image: see text] (10.0 ± 0.4 vs. 10.3 ± 0.8 l min(−1)) or LBF (5.0 ± 0.6 vs. 4.7 ± 0.5 l min(−1)); CTL: [Image: see text] increased (15.4 ± 1.4 vs. 16.9 ± 1.5 l min(−1), P < 0.01) and LBF remained unchanged (10.7 ± 1.5 vs. 10.3 ± 1.8 l min(−1)). These data suggest HF patients preferentially steal blood flow from locomotor muscles to accommodate the work of breathing during activity. Further, HF patients are unable to vasoconstrict locomotor vascular beds beyond NB when presented with a respiratory load.